2016
DOI: 10.1016/j.placenta.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of human trophoblastic extracellular vesicles and characterization of their cargo and antiviral activity

Abstract: Introduction Primary human trophoblasts release a repertoire of extracellular vesicles (EVs). Among them are nano-sized exosomes, which we found to suppress the replication of a wide range of diverse viruses. These exosomes contain trophoblastic microRNAs (miRNAs) that are expressed from the chromosome 19 miRNA cluster and exhibit antiviral properties. Here, we report our investigation of the cargo of placental EVs, focusing on the composition and the antiviral properties of exosomes, microvesicles, and apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(112 citation statements)
references
References 88 publications
4
106
1
1
Order By: Relevance
“…To examine whether our exosomeisolation module could separate EV subgroups, namely microvesicles from exosomes, we input a mixture of purified exosomes and microvesicles derived from primary human trophoblasts (PHTs) to a standalone exosome-isolation module. The isolation and culture of PHT cells from human placentas and the purification of PHT-derived microvesicles and exosomes from PHT-conditioned medium were described elsewhere (16). We identified an optimized driving frequency of 39.4 MHz based on pilot experiments using a nanoparticle mixture of 110 and 340 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To examine whether our exosomeisolation module could separate EV subgroups, namely microvesicles from exosomes, we input a mixture of purified exosomes and microvesicles derived from primary human trophoblasts (PHTs) to a standalone exosome-isolation module. The isolation and culture of PHT cells from human placentas and the purification of PHT-derived microvesicles and exosomes from PHT-conditioned medium were described elsewhere (16). We identified an optimized driving frequency of 39.4 MHz based on pilot experiments using a nanoparticle mixture of 110 and 340 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Exosomes were isolated from whole-blood specimens using an OptiPrep gradient ultracentrifugation as previously described (16). The collection of placentas used for cell isolation and culture was reviewed and approved by the Institutional Review Board (IRB) at the University of Pittsburgh.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary syncytiotrophoblasts isolated from full-term placentas potently resist infection by diverse viruses and confer broad antiviral resistance to non-trophoblast cells through effectors that operate in a paracrine manner (Bayer et al, 2015; Bayer et al, 2016; Delorme-Axford et al, 2013; Ouyang et al, 2016). Accordingly, the syncytiotrophoblast layer of first-trimester chorionic villi is largely resistant to HCMV infection, whereas CTBs and other cells of the villous core are susceptible (Fisher et al, 2000).…”
Section: Syncytiotrophoblaste As a Barrier To Vertical Transmissionmentioning
confidence: 99%
“…In most cases, the mechanistic basis for this restriction is unclear, largely given the difficulties in working with trophoblasts at various stages of gestation and modeling the human placenta using small animals. In experiments with primary syncytiotrophoblasts from full term placentas, we discovered that these cells resist viral infections and transfer this resistance to non-placental cells in a paracrine manner through pathways involving placental-specific miRNAs packaged in exosomes as well as type III interferons (IFNs) (Bayer et al, 2015; Bayer et al, 2016; Delorme-Axford et al, 2013; Ouyang et al, 2016). Others have shown that the physical properties of the syncytium function in the restriction of microbial infections.…”
Section: Syncytiotrophoblast Defensesmentioning
confidence: 99%